Digital forensics and cyber crime : 9th International Conference, ICDF2C 2017, Prague, Czech Republic, October 9-11, 2017, Proceedings /: 9th International Conference, ICDF2C 2017, Prague, Czech Republic, October 9-11, 2017, Proceedings. (2018) - Unknown
No abstract available